Applications of Scheimpflug Imaging in Glaucoma Management: Current and Potential Applications - Alexander T. Nguyen; Tiffany Liu; Ji Liu (Journal of Ophthalmology)
Scheimpflug photography is the basis for a variety of imaging devices that are highly versatile. The applications of Scheimpflug imaging are wide in scope, spanning from evaluation of corneal ectasia to quantifying density in nuclear sclerotic cataracts. The potential uses for Scheimpflug-based devices are expanding and a number of them are relevant in glaucoma. In particular, they can provide three-dimensional image reconstruction of the anterior segment which includes assessment of the iridocorneal angle. Photographic analyses allow also for a noncontact method of estimating central corneal thickness (CCT) and intraocular pressure (IOP), as well as the study of various corneal biomechanical properties, which may be useful for stratifying glaucoma risk.